(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
There are certain unique challenges when teaching programming at the university beginning level, such as the vast range of student’s prior knowledge, fear of programming, issues with syntax in programming languages, etc., as demonstrated by several earlier studies in our online survey. Several methods and resources have already been created to help students learn programming ideas more easily. These include various visual aids, guidance, video lectures, and even brand-new programming languages. Rather than using ordinary IDEs, our method is centered on the development of specialized learning interfaces for common programming languages like C++. It should be easier for professors to assist their students before they accumulate a lot of syntax and logical errors thanks to this interface, which should also prevent many of the common mistakes that students make when learning programming.